The production of gospel music: An ethnographic study of studio-recorded music in Bellville, Cape Town - Thompson, Robin L. (University of the Western Cape, 2016)
Magister Artium - MA === This thesis explores the production of music with musicians, singers and music producers who adhere to and promote Pentecostalist Christianity. The music they produce is a recently emerged genre, which I call 'Pentecospel'. I have coined this term to refer to a contemporary form of religiously inspired popular music, which is performed by young musicians belonging to various Pentecostal churches in Cape Town. I argue that 'Pentecospel' music is an emergent social form of self-representation, which is framed around Pentecostalism and the sound of Cape Town, as identified by Martin (2013). Young musicians and singers in Cape Town are absorbing and appropriating global styles of music, concepts and beliefs and music making techniques within their own musical compositions and transform their music performances in a way that enhances their local popularity. Thus, I elaborate on the processes of production through technical and social interpretations. This thesis will explore how performance, engaging audiences, the social interaction between people and technology, and the creation of their own unique sound on their musical instruments are linked to visual approaches located in the anthropology. This thesis is based on ethnographic fieldwork which took place mostly between December 2014 and February 2015. During this period, I worked with music producers and young people who have recorded at the 'Sounds of the Nations Africa: Cape Town' recording studio in Bellville, Cape Town, sharing their experiences of everyday life in and outside the studio. My three month long fieldwork included in-depth interviews, conversations and discussions, photographic and video material, and activity field notes. I made use of these methods in order to record my observations in the recording studio, during rehearsals and in public performances focusing on the social and musical interaction with the performing artists I got to know, through participant observation. I include my own participation as a musician and audience member with the use of these methods, in recording music in the 'Sounds of the Nations' recording studio for their upcoming album "Sound of Africa" and in public performances.